The efficiency of public spending on education : Lower and higher secondary education - Gałecka, Małgorzata; Kuropka, Ireneusz; Szabela-Pasierbińska, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
Research on the efficiency of public spending on the education sector hardly addresses the territorial distribution of educational attainment. This paper tries to fill in the gap by verifying whether the analysis of spatial differentiation of educational attainment could provide crucial information on the financial policy in this sphere and assess the impact of the socio-economic factors upon the education level evaluated through school tests. Our article aims to identify the relationship between spending on public education and the degree of educational attainment and inter-regionalinequality in Poland. The research results showed that the spatial approach should not be ignored when assessing the relationship between public education expenditure and the degree of educational achievement. We note that the applied public financing of second-level education in Poland does not reduce regional disparities in education but maintains them at a constant level.
Keywords: secondary education; efficiency; public expenses; DEA; Malmquist index interregional comparison